(untitled) (Biological Sciences - PJSIR, 2024)
The production of rice (Oryza sativa L.) contributes significantly to Pakistan’s food supply and foreign exchange revenues. It produces about US2 billion in foreign exchange annually and is planted on almost three million hectares each year. There is an urgent need to boost productivity per unit area in light of the increasing population rise. Since the 1980s, when hybrid rice (HR) was successfully discovered and commercialized, China’s rice production has expanded significantly. HR has been adopted in certain Asian nations up to this point, including Pakistan, India and Bangladesh. Within a few years, HR occupied 20% of Pakistan’s entire rice-growing land. The article examines the current state of China’s marketing of HR seeds in Pakistan, analyses the development and use of seeds, reviews HR export trends, extensive detail on business trends, prospects and upcoming challenges.